The effect of adding palm oil fly ash to the development of strength on oilwell cement - Shahrudin, Shahrin; Samsuri , Ariffin; Suhaimi, Ahmad; Nasir, Abu Samah; Ahmad, Zainuddin (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1994)
Calcareous and argillaceous are raw materials used in making oilwell cement class G with their main chemical compound consists of Tricalcium silicate, Dicalcium silicate, Tricalcium aluminate and Tetracalcium aluminoferrite. Pozzolanic reactions existed in some of the fly ashes when added with water helps improving the cement strength when they are added to cement. Therefore, palm oil ash a locally waste material is chosen for the study. Chemical analysis according to ASTM C 115 were carried out to determine the composition. Compressive strength tests were carried out according to American Petroleum Institute Specification 10 and were conducted at simulated reservoir condition. The analysis and the results proved that palm oil fly ash is a pozzolan material and can be used to improve the strength and development of the oilwell cement.